Exploring the Usability of Peanut Shells as an Alternative Component for Manufacturing Pattern Paper - Veronica Calasang; Vivian Arnaiz; Raymond Espina; Sheen Villavelez; Angeline Gutang; Charymae Paquit (Journal of Educational Technology Innovation and Applications, 2026)
This study explored the feasibility of utilizing peanut shells as an alternative component in the production of pattern paper for clothing construction. The research specifically aimed to determine the prospective usability of peanut-shell-based pattern paper, evaluate its marking performance after trial testing, examine the relationship between usability and marking performance, and propose recommendations based on the results. The study employed a descriptive–experimental research design and was conducted at a state university in Cebu City, Philippines.  A total of 38 respondents, consisting of 17 fashion students, 2 cutters, and 19 sewers, were selected through convenience sampling. Data were gathered using a researcher-developed survey questionnaire that underwent pilot testing to ensure its validity and reliability. The collected data were analyzed using both descriptive and inferential statistical methods, including frequency counts, percentages, mean scores, ranking, and Pearson's correlation coefficient. Findings revealed that the peanut-shell-based pattern paper demonstrated satisfactory usability and effective marking performance during pattern drafting activities. Participants described the material as flexible, durable, and capable of producing visible and clear markings using common drafting tools. Statistical analysis also indicated a positive relationship between usability and marking performance. Overall, the results suggest that peanut shells can be processed into a practical and environmentally sustainable substitute for conventional pattern paper in garment construction.